Comparison of the effects of high tibial osteotomy with and without a tourniquet - Huiwen Wu; Fangyuan Wang; Shihao Deng; Shuai Liang; Shaoze Lan; Kenan Sun; Ciren Lunzhu; Dawa Cangjue; Jun Li (BMC Surgery)
Abstract Background Tourniquets are routinely employed to achieve hemostasis in modern limb surgeries. Nevertheless, the precise role and benefits of tourniquets in high tibial osteotomy (HTO) surgeries remain understudied. The aim of this study was to assess the application of tourniquets in high-tibial osteotomy procedures. Methods This was a prospective study of patients who underwent HTO surgery at an identical hospital. The participants were randomly assigned into two groups: Group A, with a tourniquet (n = 43); and Group B, without a tourniquet (n = 43). The same surgical technique and postoperative care were employed for both groups of patients. Knee range of motion (ROM) and pain were assessed by utilizing a visual analogue scale (VAS) after exercise and maximum calf circumference, and postoperative Hospital for Special Surgery (HSS) score, as well as inflammatory markers including CRP and IL-6, were adopted to compare and analyse the recovery of knee function in the two groups of patients following surgery. Results All participants were followed up for a period exceeding three months. No cases of vascular or nerve injuries were observed during surgery in either group. Moreover, there was no statistically significant difference in total blood loss volume throughout treatment or haemoglobin or haematocrit levels (P > 0.05). furthermore, Group A underwent a shorter operation than Group B did (P < 0.05). Group B demonstrated decreased postoperative visual analog scale (VAS) pain levels, calf swelling (P < 0.05), increased early knee range of motion (P < 0.05), and diminished release of blood inflammation markers(IL-6 and CRP) (P < 0.05). Conclusion The application of tourniquets in HTO surgery reduces intraoperative blood loss and shortens the operative time yet does not substantially affect total bleeding. Nonetheless, the absence of a tourniquet resulted in reduced postoperative pain and facilitated early rehabilitation of knee function.